2011
DOI: 10.1088/1468-6996/12/6/065003
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2-loaded silica nanotube fibrous meshes for bone generation

Abstract: Silica nanotube fibrous meshes were fabricated as multiple functional matrices for both delivering bone morphological protein-2 (BMP-2) and supporting osteoblast attachment and proliferation. The meshes were fabricated via a collagen-templated sol-gel route and consisted of tubular silica with open ends. BMP-2 was loaded to the meshes by soaking in BMP-2 solution. The meshes effectively enabled the attachment and proliferation of osteoblast MC3T3-E1 cells and delivered bioactive BMP-2 to stimulate cell differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…It was found that the surface morphology of the samples depended on the type of microfluidic chips. In the case of a flat Teflon chip, the silica nanotube membranes exhibited a similar flat and smooth surface (figure 2(a)) with a porous and fibrous structure (inset) owing to the template role of the collagen fibrils, as was found in the previous studies [11, 14]. In the case of a microgrooved PDMS chip, no clear microgroove structure was found in figure 2(b).…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…It was found that the surface morphology of the samples depended on the type of microfluidic chips. In the case of a flat Teflon chip, the silica nanotube membranes exhibited a similar flat and smooth surface (figure 2(a)) with a porous and fibrous structure (inset) owing to the template role of the collagen fibrils, as was found in the previous studies [11, 14]. In the case of a microgrooved PDMS chip, no clear microgroove structure was found in figure 2(b).…”
Section: Resultssupporting
confidence: 61%
“…Silica-coated collagen hybrid fibril hydrogels were fabricated by the method described previously [11, 14], by coating collagen fibrils with silica in a Stöber-type sol–gel system consisting of tetraethylorthosilicate (TEOS; 1 ml), ethanol (9 ml), water (9 ml) and ammonia (28%, 0.5 ml) at room temperature for 24 h. Subsequently, they were placed on either a microgrooved PDMS microfluidic chip or a microgrooved Teflon microfluidic chip (1 cm × 1 cm) and subjected to a loading force of 5 N at 50 °C for 2 h to produce the microgrooved silica-coated collagen hybrid fibril membranes. After calcination at 600 °C for 2 h, the collagen fibrils were completely removed from the silica-coated collagen hybrid fibril membranes and the microgrooved silica nanotube membranes were obtained in situ .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations